Aluminum casting antifriction alloys with increased capacity to adaptability of friction surfaces - A. E. Mironov; I. S. Gershman; E. I. Gershman; S. M. Zakharov; P. A. Podrabinnik (Вестник Научно-исследовательского института железнодорожного транспорта, 2017)
The possibility of changing bronze in the manufacture of monometallic cast plain bearings with multicomponent aluminum antifriction alloys is considered. Due to alloying of aluminum with tin, lead, copper, zinc, silicon, magnesium and titanium, it was possible to create alloys with increased ability to adapt friction surfaces. According to laboratory tests, the main results of which are given in the article, it is proved that aluminum alloys on a complex of mechanical and tribotechnical properties are close or superior to the investigated bronze BrO4C4S17. Laboratory tests have shown the possibility of manufacturing monometallic plain bearings from experimental cast aluminum alloys, which by mechanical properties are not inferior to the most solid among antifriction bronzes - bronze BrO4C4S17. On a complex of tribotechnical properties, experimental alloys exceed bronze. Due to their high-fusibility, lower density, lower cost and better workability, aluminum alloys have an almost 3-5-fold advantage over economic indicators before tin bronzes. The scope of the proposed alloys will be determined in the course of bench and operational tests. To date, an experimental batch of monometallic bearings of turbochargers TK 33N-02 has been manufactured from the alloy of the AO6S3M4CT series of “Spets Dizel Servis” (Novosibirsk), which successfully passed the bench tests. Bushings 3404.00.112, 3404.00.032 and bearings 3409.00.20, made from an experimental alloy, showed the possibility of replacing the standard bronze BrO8S12 in these turbochargers. It is advisable to carry out operational tests of bearing sleeves from the alloy AO6S3M4CT for turbochargers TK 34, TK 30 and TK 33, as well as bearing inserts for diesel locomotives.